PENGARUH SEMANGAT KERJA DAN KONFLIK KERJA TERHADAP EFEKTIVITAS KERJA KARYAWAN PADA PT. SURYA BRATASENA PLANTATION PELALAWAN - Meicha Amelia Putri; Nuryanti '; Ahmad Rifki (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose this study was to determine how influence Spirit Of Work And Conflict Of Work To Effectiveness Work Employees Part Of Production At PT. Surya Bratasena Plantation Pelalawan. Its Population is all employees part of production at PT. Surya Bratasena Plantation amounting to 175 people. While method intake of sampel in this research [is] by using formula of slovin [is] so that obtained [by] sampel counted 122 people. Data analysis use doubled linear regression constructively program of SPSS. Pursuant to result of data analysis known that Spirit of work and conflict of work have an effect on to effectiveness work employees at PT. Surya Bratasena Plantation Pelalawan, Spirit of work have an effect on to effectiveness work employees at PT. Surya Bratasena Plantation Pelalawan, and Conflict of work have an effect on to effectiveness work employees at PT. Surya Bratasena Plantation Pelalawan. As for given by suggestion is writer pursuant to result of analysis taken is as follows: To maximize effectiveness work employees at PT. Surya Bratasena Plantation Pelalawan, company head shall give motivation and training so that employees always work effectively and efficient so that this matter will improve effectiveness work employees, To maximize the spirit of work employees at PT. Surya Bratasena Plantation Pelalawan, expected to company head so that emphasizing to all its subordinate to is to assisting each other or cooperate in working.Keywords : Spirit, Coflict, Expenses Work and Effectiveness